Analisis Resepsi Pasangan Pernikahan Beda Negara Terhadap Multikulturalisme Dalam Vlog Kimbab Family - Linda Yunia (Peneliti.net, 2023)
One interesting phenomenon is the rise of mixed marriages which are very common in the world and even in Indonesia. Mixed marriage couples show their existence by uploading their multicultural family life on various platforms, one of which is through Youtube vlog content. An interesting vlog to research is a vlog from the Youtube channel Kimbab Family. Kimbab Family is a Youtube channel owned by the family of a mixed marriage couple from Indonesia and South Korea. Not only does it provide a Caucasian title, the content provides knowledge for many people who try to communicate the message of multiculturalism displayed in the vlog, starting with the differences that exist in the family of this mixed marriage couple used to respect each other and prioritize the plurality of cultures, languages, and traditions that exist to the audience with family cooperation in creating harmony in diversity. The purpose of this research is to find out how the mixed marriage couple's acceptance of multiculturalism in the Kimbab Family vlog on Youtube. From the results and discussion of the research, it was found that the interpretation of mixed marriage couples towards multiculturalism in Kimbab Family vlogs is arguably diverse according to the frame of reference and field of experience of each informant. This research uses qualitative research methods with Stuart Hall's reception theory where audience reception is grouped into three positions: dominant hegemonic position, negotiated position, and oppositional position.